Sustainable Approaches for the Synthesis of Functionalized Xanthene Derivatives with Anticancer Activities Using Modern Green Tools at Room Temperature: Less Energy and More Efficiency - Majhi, Sasadhar (Synlett, 2025)
Functionalized xanthenes occupy an important position in medicinal chemistry due to their wide range of pharmacological properties. The xanthene skeleton is present in various bioactive natural products such as mulgravanols A and B, hermannol, (+)-myrtucommulone D, homapanicones A and B, blumeaxanthene II, acrotrione, etc. Important xanthene-based drugs, including propantheline bromide, methantheline, phloxine B, etc., are available on the market. Thus, much effort has been dedicated to generating or modifying xanthenes as crucial O-heterocyclic compounds. Recently, the development of efficient processes for the synthesis of xanthene derivatives using modern techniques has received significant attention in an effort to overcome the disadvantages of traditional methodologies. Aligned with the sixth principle of green chemistry, in which minimum energy is needed to perform synthetic methods at ambient temperature with optimum productivity, this account focuses on green, room-temperature strategies for the synthesis of xanthenes with anticancer activities using modern synthetic methodologies. 1 Introduction2 Synthesis of Functionalized Xanthene Derivatives through Green Strategies at Room Temperature3 Medicinal Perspectives on Functionalized Xanthene Derivatives as Anticancer Agents4 Conclusion5 List of Abbreviations
Keywords: bioactive O-heterocycles; functionalized xanthenes; ambient conditions; anticancer agents; sustainable chemistry; medicinal impact